2021
DOI: 10.3390/su13126670
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Dimensions of Unpaid Activities: An Empirical Insight into Rural Bangladesh Households

Abstract: Women in Bangladesh are generally perceived as caregivers, often confined within the households to perform various activities, whereas men are perceived as the providers. These complex gendered roles intersect with multiple factors such as household structure, marital status, religion, cultural beliefs, economic shocks, and livelihood opportunities. This study used the feminist political ecology framework to contextualize and analyze time allocated toward unpaid works, culturally accepted as female/gendered ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Also, it is a known fact that women in general and female child, particularly in India and generally in all developing countries of the world face enormously greater shares of unpaid household responsibilities that have high opportunity costs as they are unable to attend schools and build their lives and careers to same levels as that of the men in their respective societies (Sharma, 2020(Sharma, , 2021. This eventually puts the women and girls at higher risks of poverty and cyclic economic deprivation, thence posing risks toward attaining gender equity (Islam & Sharma, 2021;Sharma, 2020Sharma, , 2021. Achieving overall well-being and socio-economic equality for gender is one of the 17 Sustainable Development Goals of the United Nations.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Also, it is a known fact that women in general and female child, particularly in India and generally in all developing countries of the world face enormously greater shares of unpaid household responsibilities that have high opportunity costs as they are unable to attend schools and build their lives and careers to same levels as that of the men in their respective societies (Sharma, 2020(Sharma, , 2021. This eventually puts the women and girls at higher risks of poverty and cyclic economic deprivation, thence posing risks toward attaining gender equity (Islam & Sharma, 2021;Sharma, 2020Sharma, , 2021. Achieving overall well-being and socio-economic equality for gender is one of the 17 Sustainable Development Goals of the United Nations.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Simultaneously, other research has also indicated that despite adequate educational attainment and technical skills, women across the globe have continued to face occupational discrimination across industries (HTTP1, HTTP2). Even though women have economically been part and parcel of their households and family incomes since ages, largely contributing through their undervalued and unrecognized unpaid works (Islam & Sharma, 2021 , 2022 ; Kantor, 2009 ), it is no surprise that their gains in earnings have had to tread through far larger burdens of discriminations and biases in a society that still favors and pays males over females, even within feminine industries (Coe et al, 2012 ; Sharma, 2021a , 2021b ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, research has also indicated that despite adequate educational attainment and technical skills, women across the globe have continued to face occupational discrimination across industries [15,16]. Women have economically always contributed to the larger society through paid and unpaid work [17]. Now, even though women have started reaping the benefits of their improved skills and educational attainments by increasing their participation in male-dominated industries, more progress is required to attain gender equity and parity across non-traditional industries so that economic parity can be achieved [2].…”
Section: Post-fordism and The Origin Of Gender Disparitymentioning
confidence: 99%
“…Gender differences across occupations and their restricted participation as paid labor in industries has drawn international attention from economists and social scientists in recent times [17][18][19]. Women continue to be severely underrepresented at almost every level in corporate America, even though their educational attainments have increased significantly over three decades, and despite women's improved shares in post-high school and collegiate-level education over those of men, their participation in some of the traditionally masculine occupations and industries have not changed proportionately [20,21].…”
Section: Global and Local Perspectives On Gendered Economic Inequalitiesmentioning
confidence: 99%
See 1 more Smart Citation